Current Objectives of Canadian Federal Manpower Programs - Jain, Harish; Hines, Robert (Relations industrielles / Industrial Relations, 1973)
In this paper some of the factors leading to renewed interest in Manpower in the 1960's are enumerated ; the present course of Federal Manpower Programs is examined and the objectives of these programs are evaluated. It is suggested that the emphasis of the Federal Manpower Programs on economic growth and stabilization of the economy is misguided ; that the Department of Manpower and Immigration has failed to foresee shifts in labour market composition ; and that in the face of counter-productive fiscal policy, manpower programs and objectives as originally conceived do not have the capability to resurrect a sick economy.